Analysis of volatile flavor components and safety evaluation of Gastrodia elata Lujiu - LI Xue, LI Youjuan, WANG Yu, YANG Juan, LI Donghai, WEN Ping, TIAN Tao, HE Juan, LI Lilang (Zhongguo niangzao)
Gastrodia elata Lujiu was prepared with G. elata, American ginseng and wolfberry as raw materials, and strong-flavor (Nongxiangxing) Baijiu as base liquor. The volatile flavor components of 5 different production batches of base liquor (1#-5#) were detected. The key volatile flavor components (ROAV>1) were analyzed in combination with the relative odor activity value (ROAV) to screen the optimal base liquor. The volatile flavor components of the G. elata Lujiu prepared by the base liquor were analyzed, and its safety was evaluated. The results showed that a total of 79 volatile flavor components and 13 key volatile flavor components were detected in the 5 base liquors. Among them, base liquor 5# had the richest variety of volatile flavor components (45), including 12 key volatile flavor components. A total of 68 volatile flavor components were detected in G. elata Lujiu prepared by the base liquor 5#. Among them, there were many types of alcohols and esters (22 and 21), with relative contents of 79.33% and 11.36%, respectively. The results of the safety evaluation indicated that no poisoning symptoms or death occurred in the mice, and there was no significant difference in organ indices (P<0.05). The maximum tolerated dose (MTD) was>8 260 mg/kg body mass, and the degree of pathological damage to the liver tissue of mice was relatively mild. Therefore, G. elata Lujiu prepared by the base liquor 5# presented a harmonious and complex aroma with a distinct sauce flavor and rich and mellow taste, and it maintained a unique plant-based fortified Lujiu style, with relatively high safety.